Human papillomavirus‐stratified analysis of the prognostic role of miR‐21 in oral cavity and oropharyngeal squamous cell carcinoma. (19th September 2014) - Ko, Yoon Ho; Won, Hye Sung; Sun, Der Sheng; An, Ho Jung; Jeon, Eun Kyoung; Kim, Min Sik; Lee, Han Hong; Kang, Jin Hyoung; Jung, Chan Kwon
<x xml:space="preserve">Abstract</x> Human papillomavirus (HPV) infection plays a significant role in the development and progression of head and neck squamous cell carcinoma (HNSCC). Expression of miR‐21 has a prognostic role in a wide variety of cancers. The upregulation of miR‐21 suppresses a number of target genes, including phosphatase tensin homologue (PTEN) and programmed cell death 4 (PDCD4). We investigated the association between the expression of miR‐21 and the clinical features of HNSCC using stratified analysis based on HPV infection status. HPV status and miR‐21 expression in HNSCC tissues from 167 patients were evaluated using in situ hybridization. The expression of PDCD4 and PTEN was examined by immunohistochemistry. The up‐regulation of stromal miR‐21 expression occurred in 40.6% of HPV‐negative samples and 28.3% of the HPV‐positive group. In HPV‐stratified multivariate analysis, high miR‐21 expression was associated with poor cancer‐specific survival in HPV‐negative tumors, but not in HPV‐positive tumors. There was a significant association between miR‐21 and cytoplasmic PDCD4 overexpression in HPV‐negative HNSCCs. We suggest that stromal miR‐21 expression is an independent prognostic factor in HPV‐negative tumors and miR‐21 may play different roles depending on HPV infection status.